Fetch - Cawthon, Scott, 1971-; Waggener, Andrea Rains, 1960-; West, Carly Anne (Cawthon, Scott, 1971- Five nights at Freddy's. Fazbear frights, 2020)
Three more bone-chilling novella-length tales to keep even the bravest Five nights at Freddy's player up a night. Three boys -- Greg, Alec, and Oscar -- each have a problem that an item from Freddy Fazbear's Pizza might solve ... if they can survive the trip!